2015
DOI: 10.1159/000438945
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgolide B Reduces the Degradation of Membrane Phospholipids to Prevent Ischemia/Reperfusion Myocardial Injury in Rats

Abstract: Platelet-activating factor (PAF), a bioactive phospholipid, plays an important role in the integrity of the cellular membrane structure, and is involved in the pathogenesis of myocardial ischemia/reperfusion (IR) injuries. In this study, we tested the hypothesis that blockage of PAF receptor by BN 52021 (Ginkgolide B) can prevent IR-induced degradation of the myocardial membrane phospholipid, and deterioration of the cardiac function. Rat hearts in situ were subjected to 5 min ischemia and followed by 10 min r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…Ginkgolide B (GB) is a primary active monomer of ginkgolide that inhibits the activity of platelet-activating factor (PAF) by binding to its membrane receptor ( 15 ). BN 52021 has a protective effect against myocardial ischemia/reperfusion (IR) dysfunction ( 16 ), cerebral ischemic damage and the neurological deficits of mice after middle cerebral artery occlusion (MCAO) ( 17 ). GB also efficiently alleviates spinal cord injury by inhibiting STAT1 expression ( 18 ) and protects human umbilical vein endothelial cells via pregnane X receptor activation ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ginkgolide B (GB) is a primary active monomer of ginkgolide that inhibits the activity of platelet-activating factor (PAF) by binding to its membrane receptor ( 15 ). BN 52021 has a protective effect against myocardial ischemia/reperfusion (IR) dysfunction ( 16 ), cerebral ischemic damage and the neurological deficits of mice after middle cerebral artery occlusion (MCAO) ( 17 ). GB also efficiently alleviates spinal cord injury by inhibiting STAT1 expression ( 18 ) and protects human umbilical vein endothelial cells via pregnane X receptor activation ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ginko biloba has been widely used for the treatments of ischemic stroke and nerve system diseases . In recent study of Huang et al, the authors also inferred that Ginko biloba could promote hair growth in model mice .…”
Section: Discussionmentioning
confidence: 99%
“…Ginkgo biloba is a widely used traditional medicine for treatments of ischemic stroke and nerve system diseases . Previous study showed that the administration of Ginkgo biloba extract dramatically increased vascular endothelial growth factor (VEGF) production and improved hair growth in C57 mice .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, PAF has been reported to play an important role in many pathophysiological processes including cerebral edema and cerebral ischemia-reperfusion injury through interactions with PAFR1718. PAFR, which belongs to G protein coupled receptors superfamily, is a seven transmembrane proteins that expressed extensively throughout the brain including microglia and neurons and has been reported to be activated by interating with PAF1920. To determine the relationship between PAF and the inflammatory response after TBI, we explored development of inflammation in the brain of PAFR knockout in which the effects had on cognitive function.…”
mentioning
confidence: 99%